INOVASI PEMBELAJARAN MATEMATIKA MENGGUNAKAN GOOGLE CLASSROOM : A SYSTEMATIC LITERATURE REVIEW - Dewi Sri Wahyuni; Nurhalida Sartika (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study is to conduct systematic literature on mathematics learning innovation using google classroom. The research method is the SLR (Systematic Literature Review) method. Data collection is done by documenting and reviewing all articles related to Mathematics Learning and Google Classroom published in brackets in 2019-2020. Based on a search of various articles on the Google Scholar database, twelve (12) articles were obtained. The results of this study are a discussion of the findings that occur in the article. Based on the research conducted, the results of this study indicate that (1) learning mathematics using google classroom has a significant effect on learning so that learning is effective, characterized by high student participation and various positive attitudes that exist in students. (2) learning mathematics using google classroom is very good for learning outcomes and learning motivation of an educator. But it still has to be improved considering that there are still many learning facilities and infrastructure that do not support it, as well as abstract mathematical objectsneeded to click the link and watch the videos in YouTube